Kinetics of Oxidation of Furfural by 1-Bromobenzimidazole - Santhosh Kumar, V.; Rukmangathan, M.; Ramkumar, B. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of furfural with 1-bromobenzimidazole (BBI) has been studied in binary solvent mixture of acetic acid and water. The reaction shows uni order dependence each with respect to oxidant, substrate and H+ concentration. Addtion of benzimidazole has no effect on the reaction rate. BBIH+ has been postulated as the reactive oxidizing species. Increase in ionic strength has no effect on the reaction rate. The reaction rate increases with increase in percentage of acetic acid. The reaction fails to initiate polymerization of acrylonitrile. The reaction rates were determined at different temperatures and the activation parameters have been calculated. A mechanism in consistent with the kinetic data has been proposed.